1991
DOI: 10.5032/jae.1991.04002
|View full text |Cite
|
Sign up to set email alerts
|

Enrollment Issues In Agricultural Education Programs And FFA Membership

Abstract: No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 2 publications
1
20
1
Order By: Relevance
“…This limited viewpoint could did have some positive attributes. The members did not experience negative FFA stereotypes (Hoover & Scanlon, 1991;Phelps, Henry, & Bird, 2012); they were not put-off by rural-centered topics of FFA (Martin & Kitchel, 2013) nor were they intimidated by the overall white membership of FFA (Lawrence, Rayfield, Moore, & Outley, 2013). These conclusions seemed to counter the findings of other organizational culture studies (e.g., Maier, 1999;Simpson, 1998) as these members were willing to become active in FFA.…”
Section: Research Question One: Negotiating Connection (Or Lack Therecontrasting
confidence: 55%
See 3 more Smart Citations
“…This limited viewpoint could did have some positive attributes. The members did not experience negative FFA stereotypes (Hoover & Scanlon, 1991;Phelps, Henry, & Bird, 2012); they were not put-off by rural-centered topics of FFA (Martin & Kitchel, 2013) nor were they intimidated by the overall white membership of FFA (Lawrence, Rayfield, Moore, & Outley, 2013). These conclusions seemed to counter the findings of other organizational culture studies (e.g., Maier, 1999;Simpson, 1998) as these members were willing to become active in FFA.…”
Section: Research Question One: Negotiating Connection (Or Lack Therecontrasting
confidence: 55%
“…This challenge may include changing urban students' negative perceptions of FFA. For instance, a survey of 540 FFA members from across the nation revealed that the image of FFA was a barrier to student participation (Hoover & Scanlon, 1991). More recent studies have complemented these findings.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Past studies have indicated numerous factors influencing student enrollment behaviors including parents, friends, and significant others (Luft & Geise, 1991;Marshall, Herring, & Briers, 1992;Reis & Kahler, 1997); circumstantial/disavowance reasons (Marshall, Herring, & Briers, 1992); interests (Connors, Moore, & Elliot, 1989;Marshall, Herring, & Briers, 1992); image, future value, and perceptions of agriculture (Hoover & Scanlon, 1991;Talbert & Larke, 1995); and career and educational preparation, developmental skills, academic enhancement, response to social pressure, and participation in activity enhanced learning (Sutphin & Newsom-Stewart, 1995). Although these studies have identified numerous factors influencing enrollment in secondary programs of agriculture, there has been limited research efforts focused on students enrolled in secondary agricultural programs within urban areas.…”
Section: Introductionmentioning
confidence: 99%